Budgetary Slack: Mekanisme Fleksibilitas Anggaran atau Eksploitasi Asimetri Informasi? - Nugraha, Ahmad Rafli; Mukhtaruddin, Mukhtaruddin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Budgetary slack remains a pivotal and widely debated issue within management accounting, particularly in relation to its influence on resource allocation, performance evaluation, and managerial behavior. This study aims to evaluate the nature of budgetary slack by examining whether it functions as a rational mechanism that enhances operational flexibility or as an opportunistic practice driven by information asymmetry between subordinates and superiors. To achieve this objective, the research employs a Systematic Literature Review (SLR) approach by analyzing empirical studies published between 2020 and 2025, predominantly sourced from SINTA-indexed journals and Google Scholar databases. The review focuses on identifying key behavioral factors, organizational conditions, and control mechanisms that contribute to the emergence and persistence of budgetary slack within organizations. The findings reveal a complex and multidimensional phenomenon. On one hand, budgetary slack can serve as a strategic buffer that allows managers to cope with environmental uncertainty, reduce performance pressure, and maintain organizational stability. In uncertain and dynamic environments, the presence of slack may facilitate more realistic planning and prevent dysfunctional decision-making. On the other hand, budgetary slack is often criticized for encouraging opportunistic behavior, where subordinates intentionally underestimate capabilities or overestimate resource needs to create easily achievable targets, thereby maximizing personal benefits. This study concludes that the overall impact of budgetary slack is highly contingent upon the organizational context, including the effectiveness of internal control systems, the degree of organizational commitment, leadership style, and the integrity of the budgeting process.